Population genetic structure of aposematic alpine wood tiger moths (Parasemia plantaginis) - Ashrafi, Roghaieh (2012)
Alpine landscape with natural fragmentation restricts gene flow among populations and causes spatio-genetic structuring (high genetic differentiation) in species living there. Consequently, alpine habitat fragmentation and dispersal barriers should make isolated populations such as wood tiger moth (Parasemia plantaginis) populations prone to lose genetic diversity by local adaptation and fixation of fittest phenotype in each local population. This species is also known to be aposematic. Yellow colour on the males’ hind wings in wood tiger moth is presumed to work more efficiently against visual hunting predators due to increased conspicuousness. In addition, in field experiments with wood tiger moth, females with red hind wings were avoided more than those with orange hind wings. Therefore, yellow and red phenotypes are expected to reach fixation by directional selection in each given local population. Alternatively, uniform stabilizing selection imposed by predators can lead to constant allele frequencies throughout their distribution range. However, this species are very variable across its entire distribution both locally and regionally. Despite this dramatic variation for P. plantaginis throughout its range, it is not clear if observed phenotypic variation matches genetic divergence among populations. The main objective of the thesis was to investigate the spatio-temporal population genetic structure and differentiation of P. plantaginis population over two consecutive years in different Alpine regions in Italy, Austria, and Switzerland. The investigation was conducted using the pattern of variation at 10 microsatellite loci and in a 664 bp portion of the COI gene in the mtDNA. Expected heterozygosity was high and similar within all regions. Bayesian analyses revealed just one P. plantaginis population as a whole. This was supported by pairwise FST value, AMOVA and COI results, which indicated no differentiation among populations during two successive sampling years 2009-2010. Hence, high genetic diversity and weak population differentiation suggest high gene flow and/ or high population density in P. plantaginis. We speculate that in spite of extensive gene flow, this species remain morphologically polymorphic because the homogenizing effect of high gene flow has been compensated by differential environmental and ecological selective forces along the altitudinal gradient. However, given high gene flow (both current and past), and lack of strong post-settlement selection pressure, selective forces due to altitude are not strong enough to significantly differentiate the studied population in terms of microsatellites and mtDNA.